2017
DOI: 10.1186/s13722-017-0072-2
|View full text |Cite
|
Sign up to set email alerts
|

Public sector low threshold office-based buprenorphine treatment: outcomes at year 7

Abstract: BackgroundBuprenorphine maintenance for opioid dependence remains of limited availability among underserved populations, despite increases in US opioid misuse and overdose deaths. Low threshold primary care treatment models including the use of unobserved, “home,” buprenorphine induction may simplify initiation of care and improve access. Unobserved induction and long-term treatment outcomes have not been reported recently among large, naturalistic cohorts treated in low threshold safety net primary care setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
54
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 46 publications
6
54
1
Order By: Relevance
“…Similar literature is lacking to answer this question. The closest study conducted at a New York City public hospital primary care office evaluated prescribed BPN for unobserved self-medicated home induction [18]. This 7-year study determined BPN to be feasible and safe with no serious "induction-related adverse events," consistent with our findings.…”
Section: Discussion/conclusionsupporting
confidence: 76%
See 2 more Smart Citations
“…Similar literature is lacking to answer this question. The closest study conducted at a New York City public hospital primary care office evaluated prescribed BPN for unobserved self-medicated home induction [18]. This 7-year study determined BPN to be feasible and safe with no serious "induction-related adverse events," consistent with our findings.…”
Section: Discussion/conclusionsupporting
confidence: 76%
“…In addition, the subset of patients defined "in treatment" may have continued on to treatment elsewhere prior to completing 30 days and therefore cannot necessarily be considered less successful than those "stabilized in treatment." The New York self-medicated buprenorphine study demonstrated higher "self-reported" median retention rates 38 weeks over a 7-year period as opposed to LASSO's 51.7% of patient's retention of 52 days over 6 years [18]. However, the following issues must be taken into consideration when making such a comparison: LASSO data is objective, using free BPNX on "hard to treat" patients which know they will be welcomed back with no penalty.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buprenorphine, unlike methadone, does not need to be administered in a drug treatment facility; and studies have shown that both in-office and home induction are effective [10,11]. Buprenorphine can also be combined with an antagonist naloxone to limit the recreational potential and street value, as well as potential diversion relative to methadone [11].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of premature discontinuation is also greater for clients prescribed XR-naltrexone compared to buprenorphine-naloxone (13), while only buprenorphine and methadone have been shown to reduce mortality (14). The agonist properties of methadone and buprenorphine mean they can be initiated quickly after opioid use (15,16), unlike XR-naltrexone.…”
mentioning
confidence: 99%